2009
DOI: 10.1007/s00381-008-0749-7
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow autoregulation during intracranial hypertension: a simple, purely hydraulic mechanism?

Abstract: A biphasic pattern of pulsatile intracranial pressure (pICP) was observed in all trials. Initially, until the CBF velocity remained constant, pICP increased (from 1.2 to 5.4 mmHg) following a rise in diastolic intracranial pressure (dICP); thereafter, in spite of a further rise in dICP, pICP decreased (2.87 mmHg) following CBF velocity reduction until intracranial circulation arrest (pICP=1.2 mmHg). A specular pattern was observed when the intraventricular infusion was stopped and CBF velocity returned to basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Extracellular fluid is produced during the systolic phase, and is absorbed during the diastolic phase, and an imbalance between production and absorption in favor of absorption will cause a decrease in the volume of the brain parenchyma, and a consequent increase in ventricular volume, causing hydrocephalus. In DC, when the skull is removed too close to the midline, this reduces the external force compressing the veins mainly during the diastolic phase, thus causing an increase in venous outflow, which in turn produces an increase in extracellular fluid absorption and a decrease in the volume of the brain parenchyma, which causes ventricular enlargement (Anile et al, 2009). Introducing this condition into the previously mentioned mathematical model may cause a more pronounced effect of DC on the venous outflow resistance than on the ICP reduction, and an increase in the ventricular volume is clearly evident (unpublished data presented by C. Anile at the 12th Euroacademia Multidisciplinaria Neurotraumatologica Annual Meeting, held in Rome on June 21-23, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular fluid is produced during the systolic phase, and is absorbed during the diastolic phase, and an imbalance between production and absorption in favor of absorption will cause a decrease in the volume of the brain parenchyma, and a consequent increase in ventricular volume, causing hydrocephalus. In DC, when the skull is removed too close to the midline, this reduces the external force compressing the veins mainly during the diastolic phase, thus causing an increase in venous outflow, which in turn produces an increase in extracellular fluid absorption and a decrease in the volume of the brain parenchyma, which causes ventricular enlargement (Anile et al, 2009). Introducing this condition into the previously mentioned mathematical model may cause a more pronounced effect of DC on the venous outflow resistance than on the ICP reduction, and an increase in the ventricular volume is clearly evident (unpublished data presented by C. Anile at the 12th Euroacademia Multidisciplinaria Neurotraumatologica Annual Meeting, held in Rome on June 21-23, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that vascular resistances change in response to a change in perfusion pressure [95][96][97][98][99]: increases in hydrostatic pressure are accompanied by an increase in downstream vessels resistance, whereas decreases in pressure are accompanied by decreases in resistance. This ensures stability of tissue perfusion conditions within a certain range of arterial pressure values, termed the autoregulatory zone.…”
Section: Capillary Reactivity and A Downstream Regulation Of Cbfmentioning
confidence: 99%
“…that the arterial side of cerebral vasculature is a hydraulic system [95] existing to ensure stability of capillary intravascular pressure, which allows one to predict increases in capillary flow based on its resistance changes. This is equivalent to say that the cerebral vasculature bears a feedback type of pressure control system whose propagated response (upstream) begins with changes in capillary tone (downstream) [59,60] and that flow is ultimately a function of capillary resistance.…”
Section: Capillary Reactivity and A Downstream Regulation Of Cbfmentioning
confidence: 99%
“…They considered that extracellular fluid is absorbed during the diastolic phase of the cardiac cycle, and that this causes a decrease in brain parenchyma volume and a consequent increase in ventricular volume, which causes hydrocephalus. Anile et al found that when the skull is removed too close to the midline, the external force compressing the veins mainly during the diastolic phase is reduced, causing an increase in venous outflow and extracellular fluid absorption and a decrease in brain parenchyma volume, which causes ventriculomegaly and hydrocephalus 38 . Takeuchi et al reported that the distance from the decompressive defect to the midline shows a strong trend for an association with ventriculomegaly after DC in patients who suffered from intracerebral hemorrhage (ICH) besides meningitis, but it was not an impact factor for ventriculomegaly (p=0.051).…”
Section: Mechanisms Of Hydrocephalus After DCmentioning
confidence: 99%